Exploration Study of Sharia Corporate Governance Disclosure on Bank Annual Report of Sharia Business Unit - Zulfikar, Z; Purbasari, Heppy; Puspawati, Dewita (Riset Akuntansi dan Keuangan Indonesia, 2021)
The aim of this study is to identify and investigate the disclosure of sharia corporate governance structures included in the corporate governance disclosure index (CGDI). In 2019, the sample consisted of 19 Sharia Business Unit (SBU) banks. The sharia supervisory board, board of commissioners, board of directors, auxiliary committee of the board of commissioners, internal control and external audit, risk management, and reporting on the application of corporate governance are the seven metrics included in this analysis. This research employs the content analysis process, which entails reading each sample’s annual report and then calculating the index score for each bank using a dichotomy approach. BANK CIMB Niaga received a maximum rating of 1.00 in 2019, suggesting that the bank perfectly reported 72 disclosure items from the seven indicators. The bank sample disclosure was found to be high on many dimensions, including the board of commissioners, board of directors, and auxiliary committee of the board of commissioners. On the other hand, among other things, the disclosure of sharia supervisory boards in US banks is generally lacking. The findings of this study show that the average disclosure rate among the bank sample is adequate, with an 89 percent percentage yield.